Versatility and utilities - Yaacob, Muhammad; Riasmi, Yumarnis; Ab, Karim, Muhammad Shahrim (University Putra Malaysia, 2012)
Banana fruit is known to be rich in nutrients such as minerals,sugars, vitamins and fibers. Some ripe bananas can be eaten raw and also eaten with ice cream (banana split). The fruits also can be used for cooking such as curry. It also can be processed into chips, juices or fried bananas. The fruits are also believed to be used for relieving coughs and ulcers, having diuretic effect, increasing sexual drive and stimulating the production of semen in men.